The impact of the UK aviation tax on carbon dioxide emissions and visitor numbers - Karen Mayor; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2007)
We use a model of domestic and international tourist numbers and flows to estimate the impact of the recent and proposed changes in the Air Passenger Duty (APD) of the United Kingdom. We find that the recent doubling of the APD has the perverse effect of increasing carbon dioxide emissions, albeit only slightly, because it reduces the relative price difference between near and far holidays. Tourist arrivals in the UK would fall slightly. Tourist arrivals from the UK would fall in the countries near to the UK, and this drop would be only partly offset by displaced tourists from the UK. Tourist numbers in countries far from the UK would increase. The proposal of the Conservative Party to exempt the first 2,000 miles (for UK residents) would decrease emissions by roughly the same amount as abolishing the APD altogether - but tourist arrivals in the UK would not rise. These results are reversed if we assume that domestic holidays and foreign holidays are close substitutes. If the same revenue were raised with a carbon tax rather than a boarding tax, emissions would fall with higher taxes.
Keywords: 330; International tourism; carbon dioxide emissions; boarding tax; United Kingdom; Internationaler Tourismus; Luftverunreinigung; Umweltabgabe; Kohlendioxid; Luftverkehr; Ökosteuer; Steuerwirkung; Großbritannien